Association between the ACTN3 R577X polymorphism and female endurance athletes in China - Shang, X.; Huang, C.; Chang, Q.; Zhang, L.; Huang, T. (International Journal of Sports Medicine, 2010)
The Alpha-actinin 3 (ACTN3) gene is absent in 18% of healthy white individuals owing to homozygosity for a premature stop codon polymorphism (rs1815739) and is only expressed in the Z line of fast glycolytic muscle fibres. Previous studies have shown highly significant association between ACTN3 genotype and sprint/power performance, while the nonfunctional allele (577X) was believed to provide an advantage for endurance performance. In this study we tested whether XX genotype was over-represented in Chinese endurance athletes compared to the general population. In a study of 250 Chinese endurance athletes of provincial or national competitive standard and 450 controls, we proved that the ACTN3 XX genotype (21.2 vs. 15.8%; P=0.02) and X allele (51.3 vs. 41.1%; P=0.019) were significantly over-represented in female endurance athletes compared to controls, while no genotype-related differences were observed in male endurance athletes. Besides, the frequency of the ACTN3 XX genotype (28.6%) was the highest in a group of highly elite athletes compared with other groups, which supported the hypothesis that the absence of Alpha-actinin-3 provided some sort of advantage for endurance athletes. Our results indicated that ACTN3 R577X polymorphism was associated with endurance performance in female athletes but not male athletes in China.